Status of biodiversity in wetlands of Biswanath District of Assam, India - RANJIT KAKATI; ABHISHEK BHUYAN; Dipankar Borah (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kakati R, Das N, Bhuyan A, Borah D. 2021. Status of biodiversity in wetlands of Biswanath District of Assam, India. Biodiversitas 22: 453-472. Reports on biodiversity of a region are the firsthand data to understand the assemblage, importance, and to follow conservation inputs. The present study was aimed to document and analyze the wetland biodiversity of Biswanath District of Assam, India. Data was collected from 27 wetland habitats from 2015-2019. A total of 235 taxa were recorded, of which 79 taxa (77 species, one variety, and one subspecies) were vascular plants, 83 water birds, 47 fishes, 7 amphibians, 18 reptiles, and 2 mammals. None of the plants and amphibians fall under any of the threatened categories as per IUCN Red List 2020. However, among the bird species, 2 species are assessed as endangered, 4 species as vulnerable, and 10 species as near threatened. Among the fishes, 2 are vulnerable and 3 near threatened. Among the reptiles one is extinct in the wild (EW), 3 endangered and 3 are vulnerable. Along with the checklist of the present biodiversity, past and present population trends, as well as earlier records from Assam of the threatened species, is provided. The results of this study can be used by stakeholders for species identification and as the baseline taxonomic account for future studies on the conservation of these wetland species in a global context.